A qualitative analysis of the attitudes of Irish patients towards participation in genetic-based research. (November 2016) - McVeigh, T.; Sweeney, K.; Kerin, M.; Gallagher, D.
Abstract Background Progress in diagnostic and therapeutic strategies in medicine is dependent upon high-quality biomedical research. Technological advances have facilitated improved understanding of disease aetiology, and rapidly emerging data promises further progress. Translating this potential into the clinic depends on patient participation in innovative clinical trials. We investigated attitudes to genetic research in Ireland, particularly with respect to commercial and financial implications. Methods A multi-centre, cross-sectional survey study was performed. Consecutive out-patients attending four clinics were asked to complete paper-based questionnaires. The same questionnaire was publicly available in electronic format onwww.surveymonkey.com for 72 h. Data were analysed using SPSS. Results 351 questionnaires were completed (99 paper, 252 electronic). The majority of respondents were female (n  = 288, 82 %), and highly educated, with 244 (70 %) attending college/university. Most participants supported genetic research (267, 76 %), more frequently for common diseases (274, 78 %) than rare disorders (204, 58 %, p  < 0.001, χ 2 ). 103 (29 %) had participated in scientific research, and 57 (16 %) had donated material to a bio-bank. The majority (n  = 213, 61 %) would not support research with potential financial/commercial gain. 106 (30 %) would decline to participate in research if researchers would benefit financially, compared to 49 (14 %) if the research was supported by a pharmaceutical company (p  < 0.001, χ 2 ). Respondents would provide buccal samples (258, 74 %) more readily than tissue (225, 64 %) or blood (222, 63 %). Conclusions A high level of support for genetic research exists among the Irish population, but active participation is dependent upon a number of factors, notably, type of biological material required, frequency of the disease in question, and commercial interest of the researchers.